2005
DOI: 10.1029/2005gl023804
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Polar Antarctic trends: Influence of tropical SST

Abstract: [1] The polar Antarctic atmosphere has been recently characterized by a progressive intensification of the circumpolar westerly winds, both in the stratospheric and tropospheric component. We simulate the response of the polar southern hemisphere atmosphere to a prescribed trend of oceanic equatorial temperature to demonstrate a possible link between the progressive warming of tropical sea surface temperature (SST) and Antarctic climate changes in the last decades. Model simulations produce an atmospheric resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
(43 reference statements)
0
30
0
Order By: Relevance
“…Given the strong projection of the Pacific-South American pattern upon the SAM, we suggest that the forcing attributable to SST warming in the tropical central Pacific explains a substantial part of the observed trend in the SAM in winter. Similarly, the DJF SST warming over most of the tropics along with cooling in the eastern Pacific also has the potential to excite a zonally symmetric response in the extratropics by changing the Hadley cell and the midlatitude jet stream (Seager et al 2003;L'Heureux and Thompson 2006;Grassi et al 2005), suggesting a further possible contribution of tropical SST to the SAM summer trend.…”
Section: B Dynamics Of the Sam Trendmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the strong projection of the Pacific-South American pattern upon the SAM, we suggest that the forcing attributable to SST warming in the tropical central Pacific explains a substantial part of the observed trend in the SAM in winter. Similarly, the DJF SST warming over most of the tropics along with cooling in the eastern Pacific also has the potential to excite a zonally symmetric response in the extratropics by changing the Hadley cell and the midlatitude jet stream (Seager et al 2003;L'Heureux and Thompson 2006;Grassi et al 2005), suggesting a further possible contribution of tropical SST to the SAM summer trend.…”
Section: B Dynamics Of the Sam Trendmentioning
confidence: 99%
“…For example, Grassi et al (2005) suggested that the tropical SST in austral summer has a significant impact on the SAM by altering the propagation of planetary waves, which in turn affect the midlatitude jet and hence the SAM. L'Heureux and found that SAM and El Niñ o-Southern Oscillation (ENSO)-related circulation anomalies exhibit common features during austral summer [DecemberFebruary (DJF)] and that about 25% of variance of the SAM index is related to ENSO variations.…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to an increase of the swell coming from the Southern Ocean that also explains the equatorward rotation of extreme WEF projected by the end of the XXI century in many areas of the Southern hemisphere (Figure 3). On the other hand, an intensified AAO can be associated with a warming sea surface at subtropical latitudes, involving more intense convection and more frequent storms [Grassi et al, 2005].…”
Section: 1002/2016gl072488mentioning
confidence: 99%
“…The long-term trend in tropical SST also has a correspondence to the trend of temperature in the southern polar stratosphere (Grassi et al, 2005(Grassi et al, , 2006Hu and Fu, 2009;Li et al, 2010;Clem et al, 2016). Although ENSO is reported to cause circulation and temperature anomalies in the southern high-latitude stratosphere, the interannual variability of the southern polar vortex and ozone levels over the past 3 decades cannot be explained by ENSO variations alone (Angell, 1988(Angell, , 1990Hurwitz et al, 2011a, b;Lin et al, 2012;Wilson et al, 2014;Evtushevsky et al, 2015;Yu et al, 2015;Yang et al, 2015;Welhouse et al, 2016).…”
Section: Introductionmentioning
confidence: 99%